Analisis Spasial Tingkat Bahaya Banjir Desa Amasing Kali Dengan Hec-RAS 2D - Ichsan Rauf (Universitas Negeri Gorontalo, 2021)
The phenomenon of flooding that occurs in various parts of the world continues to increase, both in terms of frequency and amplitude. Without neglecting the morphology of the region, global climate change and changes in land use as a result of economic growth are the main factors causing this disaster. Understanding flood characteristics, be it discharge, inundation height, and their distribution in an area is very important as a basis for determining flood control efforts. This study aims to analyze the level of flood vulnerability based on the characteristics of the occurred floods. Hydrological and topographical analyzes were performed as the basis for the flow hydraulics calculations performed with Hec-RAS 2D version 5.0.7. The flood distribution simulation results with return periods of 2, 5, 10, and 25 years show that the area of ​​the village that has the potential to be inundated is ± 22.57 ha, ± 37.11 ha, ± 41.81 ha, and ± 47.27 ha, with inundation heights varying between 0.25 m. – 1.50 m, which can be classified as low to high hazard.